Catering to investors through product complexity - Claire Célérier; Boris Vallée (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2016)
This study investigates the rationale for issuing complex securities to retail investors. We focus on a large market of investment products targeted exclusively at households: retail structured products in Europe. We develop an economic measure of product complexity in this market via a text analysis of 55,000 product payoff formulas. Over the 2002-2010 period, product complexity increases, risky products become more common, and product headline rates diverge from the prevailing interest rates as the latter decline. The complexity of a product is positively correlated with its headline rate and risk. Complex products appear more profitable to the banks distributing them, have a lower expost performance, and are more frequently sold by banks targeting low-income households. These empirical facts are consistent with banks strategically using product complexity to cater to yield-seeking households.
Keywords: I22; G1; D18; D12; 330; Financial Complexity; Catering; Shrouding; Reaching for Yield; Household